2017
DOI: 10.1016/j.ijppaw.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Alien freshwater fish parasites from South Africa: Diversity, distribution, status and the way forward

Abstract: The global translocation and introduction of freshwater fish into non-native regions has created the perfect opportunity for the co-introduction of their parasites. In a recent review on non-native freshwater fish introductions in South Africa, 55 fishes were reported as introduced into novel environments in South Africa, with 27 alien and 28 extralimital. However, the parasites potentially co-introduced by these non-native fishes have received much less attention from researchers than the hosts themselves. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 59 publications
0
32
0
1
Order By: Relevance
“…The introduction of 27 alien fishes to South Africa has provided opportunities for at least 23 parasitic co-introductions of ten monogeneans, eight ciliates, two cestodes, a copepod, a flagellate, and a branchiuran (Smit et al 2017). Most (16) of these parasites are not known to have infected native fishes (Smit et al 2017). For example, five ancyrocephalid monogeneans are found only on the alien Largemouth Bass, Micropterus salmoides.…”
Section: Freshwater Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of 27 alien fishes to South Africa has provided opportunities for at least 23 parasitic co-introductions of ten monogeneans, eight ciliates, two cestodes, a copepod, a flagellate, and a branchiuran (Smit et al 2017). Most (16) of these parasites are not known to have infected native fishes (Smit et al 2017). For example, five ancyrocephalid monogeneans are found only on the alien Largemouth Bass, Micropterus salmoides.…”
Section: Freshwater Fishmentioning
confidence: 99%
“…Despite the almost ubiquitous presence of bass in South African rivers (Ellender et al 2014), these parasites have not been observed to infect native fishes to date (Truter et al 2017). The other seven co-introduced parasites, however, have formed new associations with native hosts, probably because of broader levels of generalism in their symbiotic requirements (Smit et al 2017). While significant impacts on the health status of novel hosts have been documented (see Weyl et al 2020, Sect.…”
Section: Freshwater Fishmentioning
confidence: 99%
“…The common carp Cyprinus carpio, for instance, is largely recognized as being responsible for numerous co-introductions and co-invasions of different parasitic groups worldwide, including myxozoans (e.g. [50,60,68,71,76]). Reported cases of co-introduction with C. carpio include the myxobolid species Thelohanellus hovorkai Akhmerov, 1960 and T. nikolskii Akhmerov, 1955, both originally from the Amur basin and later introduced to Hungary [48,50].…”
Section: Myxobolid Biodiversity In Endemic Iberian Cypriniformsmentioning
confidence: 99%
“…Due to mixing of species from different geographic regions, disease dynamics in wholesalers, retailers and hobbyist aquaria may result in parasite host switching and increased virulence (Kelly et al 2009). Accidental or intentional introduction of exotic species into local fish populations can cause transmission of highly virulent parasites to which native fish species may be especially susceptibile 90 (Smit et al 2017). 91…”
Section: Introductionmentioning
confidence: 99%